La scène de remise du temple au dieu (rdἰ(.t) pr n=bf) dans le rituel de fondation des temples égyptiens aux époques ptolémaïque et romaine - Martzolff, Laetitia (Die Welt des Orients, 2011)
This article is studying the place of the foundation ritual in temples of the Graeco-Roman Times and is focusing specially on the final scene of the composition: the offering of the temple to the god. This scene appears as well in the context of the ritual itself as apart from the composition. In this case, the scene is represented alone, often on door jambs, but not exclusively. Comparison of textual contents shows that the topics approached in the inscriptions are identical, whatever context in which scenes appear. It proves that same models were used to compose the texts of the scenes registered in a sequence of the ritual and isolated from it. In several temples of the Late Period, the only scene of giving the temple to the god is a scene 'summary' of the whole ritual.